2022
DOI: 10.1038/s41598-022-20425-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity is a key determinant in the activity of arginine-rich cell penetrating peptides

Abstract: To deliver useful biological payloads into the cytosolic space of cells, cell-penetrating peptides have to cross biological membranes. The molecular features that control or enhance this activity remain unclear. Herein, a dimeric template of the arginine-rich HIV TAT CPP was used to establish the effect of incorporating groups and residues of various chemical structures and properties. A positive correlation is established between the relative hydrophobicity of these additional moieties and the ability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…In addition, the relative hydrophobicities of the peptides were assessed by measuring their retention times in analytical reverse‐phase high‐performance liquid chromatography (RP‐HPLC). The order of elution has been suggested to correlate well with the hydrophobicity of the folded peptides, as molecules with a higher hydrophobicity should have a higher affinity to the HPLC stationary phase [28] . Here, the retention time of EpN18‐L was the largest, and we observed an order of EpN18‐L>EpN18‐R≥EpN18≥EpN18‐L6W>EpN18‐K>EpN18‐Q>EpN18‐N>EpN18‐V (Table 1, R t ).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, the relative hydrophobicities of the peptides were assessed by measuring their retention times in analytical reverse‐phase high‐performance liquid chromatography (RP‐HPLC). The order of elution has been suggested to correlate well with the hydrophobicity of the folded peptides, as molecules with a higher hydrophobicity should have a higher affinity to the HPLC stationary phase [28] . Here, the retention time of EpN18‐L was the largest, and we observed an order of EpN18‐L>EpN18‐R≥EpN18≥EpN18‐L6W>EpN18‐K>EpN18‐Q>EpN18‐N>EpN18‐V (Table 1, R t ).…”
Section: Resultssupporting
confidence: 58%
“…The order of elution has been suggested to correlate well with the hydrophobicity of the folded peptides, as molecules with a higher hydrophobicity should have a higher affinity to the HPLC stationary phase. [28] Here, the retention time of EpN18-L was the largest, and we observed an order of EpN18…”
Section: Membrane Affinity and Hydrophobicity Of The Peptidesmentioning
confidence: 58%
“…The fluorescence that remains trapped in the endosomes is also partially masked. Recently, to facilitate quantification, we have used AlexaFluor 488-labeled Histone H1 (AF488-H1) as a probe of endosomal escape. , When co-incubated with dfTAT-like CPPs, AF488-H1 enters cells with minimal degradation and intrinsically accumulates in nuclei. The number of cells that display nuclear staining can then be counted (above a detection threshold) and a ratio of cytoplasmic/endosomal versus nuclear signal established .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a direct or indirect contribution of ST or SC in fusion. In this context, it is worth noting that the introduction of hydrophobic residues to the dfTAT structure can amplify its membrane activity . In light of this, ST and SC might impart additional hydrophobicity to 1 , thereby augmenting interactions with lipids and promoting bilayer fusion.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, numerous comparisons have been made differentiating the uptake potential of positively charged, short peptide chains against their long or net-neutral counterparts. Specifically, it was shown that short homopolymers of arginine (R) had higher uptake compared to other amino acids including polylysine chains [ 20 , 21 , 22 , 23 ]. Attempts to utilize and mimic this ability have been undertaken, achieving excellent results.…”
Section: Types Of Cppsmentioning
confidence: 99%